2015
DOI: 10.1177/1071100715611960
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes and Return to Activity After Peroneus Brevis Repair

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…[12] While surgical repair has proven to be effective, it has been reported that as many as 25.4% of patients struggle with post-op complications such as pain, and 17.4% experience persistent swelling. [2] The optimal surgical technique would be one that prevents complications effectively and allows patients to resume normal activities in a reduced amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…[12] While surgical repair has proven to be effective, it has been reported that as many as 25.4% of patients struggle with post-op complications such as pain, and 17.4% experience persistent swelling. [2] The optimal surgical technique would be one that prevents complications effectively and allows patients to resume normal activities in a reduced amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…Injury of the peroneal tendons should be considered in any patient presenting with chronic lateral ankle symptoms. Often associated with other concomitant ankle disease, abnormalities of the peroneal tendons may be overlooked in up to 40% of cases (13)(14)(15)(16). Of patients with identified peroneal tendon disease, an estimated 15%-44% will have associated ligamentous instability of the lateral ankle (13,14,17).…”
Section: Peroneus Longus and Brevis Tendonsmentioning
confidence: 99%
“…Often associated with other concomitant ankle disease, abnormalities of the peroneal tendons may be overlooked in up to 40% of cases (13)(14)(15)(16). Of patients with identified peroneal tendon disease, an estimated 15%-44% will have associated ligamentous instability of the lateral ankle (13,14,17). The peroneus brevis (PB) is the primary evertor of the foot and is more commonly subject to tendon injury than the peroneus longus (PL) (14,18).…”
Section: Peroneus Longus and Brevis Tendonsmentioning
confidence: 99%
See 2 more Smart Citations